INSTITUALIZATION OF PUBLIC LIFE IN THE CONDITIONS OF GLOBALIZATION: SOCIAL-PHILOSOPHICAL ANALYSIS - Литовченко, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
In the article social-philosophic research of the institualization features of public life are examined in the conditions of globalization. Essence of transformation of traditional social institutes is analysed under influence of globalization processes.